Visualization and quantification of cellular RNA production and degradation using a combined fluorescence and mass spectrometry characterization assay. Issue 57 (1st July 2019) - Gao, Xiaoying; Shu, Xiao; Song, Yinuo; Cao, Jie; Gao, Minsong; Wang, Fengqin; Wang, Yizhen; Sun, Jing Zhi; Liu, Jianzhao; Tang, Ben Zhong
Abstract : A combined fluorescence and mass spectrometry assay is developed to visualize and quantify cellular RNA production and degradation. Abstract : Here we report a combined fluorescence and mass spectrometry assay which is capable of stably visualizing and quantifying cellular nucleoside-labeled RNA production and degradation. The fluorescence and mass spectrometry signals from cellular labeled RNAs show a linear correlation. This simple and robust assay benefits the biological community to study RNA metabolism.